Lagu Darah Juang dalam Konteks Demonstrasi 1998 - Yusuf, Nur Fadilah (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2023)
Research on songs in Indonesian historiography rarely receives attention from historians. It is very important for author to examine songs from the historical aspects and the socio-political realities of their time. Therefore, the aim of writing this article is to discuss songs that are the reality of the demonstrators' struggle (activists, students, community leaders and other national elements) in 1998. Additionally, the author highlights this song (Darah Juang) really describes how the life of the Indonesian people was under the power of the government of the New Order era which exercised hegemony in almost all aspects of life. This research uses historical methods as a form of scientific writing which includes heuristics, source criticism, interpretation, and historiography as well. Furthermore, in this research article, there are results and discussions that the author can convey, including: 1. Relations between Arts and Politics in the New Order era, 2. Art Media in the New Order Era Demonstrations, 3. The historicity of the Songs Darah Juang, and the last one 4. Songs Darah Juang in the 1998 Demonstration.